A MATE-Family Efflux Pump Rescues the Escherichia coli 8-Oxoguanine-Repair-Deficient Mutator Phenotype and Protects Against H2O2 Killing - Guelfo, Javier R.; Rodríguez-Rojas, Alexandro; Matic, Ivan; Blázquez, Jesús (PLOS Genetics, 2010)
Author Summary Some bacteria and eukaryotic cells produce a higher-than-normal number of mutations (so-called “mutators”). Because some of the mutations produced can be favorable (such as antibiotic resistance in bacteria or resistance to anticancer drugs in human tumor cells), the high mutation rate may provide a short-term advantage. However, the production of huge numbers of mutations may compromise the future of these cells because they also accumulate disadvantageous mutations. Consequently, cells may contain backup mechanisms to reduce the accumulation of mutations. We have found that some types of hypermutable mutants can escape this fate by increasing the expression of an efflux pump predicted to export specific oxidative substances, the precursors of many mutations, and consequently reducing their number. Amazingly, this over-expression may confer several advantageous phenotypes simultaneously, such as antibiotic resistance, protection against reactive oxygen species and antimutability.